Neuroimaging in headaches: a literature review on diagnostic advances - Scabeni, Bruna Verdi; Habowski, Isabela Colissi; Vieira, Júlia Ragone; Graciliano, Larisa Melo Faiad; Corrales, Waleska Krishna Macedo (Headache Medicine, 2024)
Introduction: Headaches have become one of themost common conditions worldwide and are a primary reason for seeking medical attention. It isestimated that seven out of ten people in Brazil sufferfrom some form of headache. Accurate analysis ofthe disease is crucial for developing effectivetreatment strategies, as there are various types ofheadaches. Neuroimaging techniques such as magnetic resonance imaging (MRI), computedtomography (CT), functional magnetic resonanceimaging (fMRI), and positron emission tomography(PET) have revolutionized medicine. Their analysisprovides a comprehensive view of current and future diagnostic trends, allowing for differentiation ofheadache types and aiding in their treatment. Objective: to understand the diagnostic advances in neuroimaging for headaches. Methods: This study was a literature review utilizingPubMed, Scielo, and Scopus databases. Articlescontaining information on neuroimaging andheadaches published in the last 20 years wereselected. Results: Advances in neuroimaging provide a betterunderstanding of headaches and improve differentialdiagnosis. Functional magnetic resonance imaging(fMRI) can identify functional changes in specificbrain regions during migraine attacks (Dodick, 2018), revealing patterns of different types of headachesand enabling the understanding of chronicheadaches. The use of techniques such as magneticresonance spectroscopy (MRS) has also shownpromise. This technique can assess metabolicchanges in the brain during headache episodes, providing insight into the associated biochemicalchanges (Zhang et al., 2020). The use of artificial intelligence stands out for its potential to enhancediagnostic accuracy and personalize treatments. These algorithms can help predict treatmentresponse in patients with chronic headaches, allowing for personalized therapeutic approaches (Chen et al., 2021). Conclusion: These findings emphasize thatadvances in neuroimaging have made it possible togain a deeper understanding of headache types andthe biochemical changes that cause them. Furthermore, it is possible to expedite the diagnosticprocess and provide personalized treatment, therebyimproving the patient's quality of life.